Histological Structure of Varanus Salvator Intestine - Widyaningsih, Risti (Proceeding International Conference on Science and Engineering, 2020)
Varanus salvator is a common species in Indonesia. This animal is known as the water lizard, who is a member of the family Varanidae or known as the monitor lizard. This research aims to find out histological structure of Varanus salvator intestine. Histological observation was carried out by making histological preparations using the paraffin method. The results of this study were analyzed in a comparative descriptive manner through observation in a microscope and transverse photo histology preparations using a camera. The results of this study indicate that the intestinal histological structure of Varanus salvator consists of Serosa (Sr), Muscle layer (Ml), Muscularis externa (Me), Submucosa (Sm), Mucosa (M), Blood Vessel (Bv) dan Lamina Propria (Lp).